EFEK FAKTOR UKURAN, LIKUIDITAS, LEVERAGE, KEPEMILIKAN INSTITUSIONAL TERHADAP PROFITABILITAS PADA PERUSAHAAN SUMBER DAYA ALAM YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Riny Riny (DAS Institute, 2023)
Research aims determine the effect Size, Liquidity, Leverage and Institutional Ownership on Profitability in Natural Resources Companies listed on the Indonesia Stock Exchange 2016-2019. population amounted to 66 companies. Sampling method used was purposive sampling, obtained a sample of 19 companies, observational 95 data. Data from the financial statements of Natural Resources companies listed on the Indonesia Stock Exchange 2016-2020. Analytical method used multiple regression. Results show simultaneously Firm Size, Liquidity, Leverage and Institutional Ownership have an effect on Profitability. Partially, Leverage negative effect and Institutional Ownership positive effect, while the Firm Size and Liquidity have no effect.